The 'caring experience': Testing the psychometric properties of the Caring Efficacy Scale. Issue 6 (9th May 2014) - Reid, Carol; Courtney, Mary; Anderson, Debra; Hurst, Cameron
Abstract : The purpose of the study was to undertake rigorous psychometric testing of the Caring Efficacy Scale in a sample of Registered Nurses. A cross‐sectional survey of 2000 registered nurses was undertaken. The Caring Efficacy Scale was utilized to inform the psychometric properties of the selected items of the Caring Efficacy Scale. Cronbach's Alpha identified reliability of the data. Exploratory Factor Analysis and Confirmatory Factor Analysis were undertaken to validate the factors. Confirmatory factor analysis confirmed the development of two factors; C onfidence to C are and D oubts and C oncerns . The Caring Efficacy Scale has undergone rigorous psychometric testing, affording evidence of internal consistency and goodness‐of‐fit indices within satisfactory ranges. The Caring Efficacy Scale is valid for use in an Australian population of registered nurses. The scale can be used as a subscale or total score reflective of self‐efficacy in nursing. This scale may assist nursing educators to predict levels of caring efficacy.